Leadership Development Program for Nurses at a Health Care for the Homeless Program: An Educational Intervention. Issue 4 (2nd October 2018) - Bhalla, Pooja; Damus, Karla; LaCoursiere-Zucchero, Terri; Beauchesne, Michelle
ABSTRACT: Purpose: This quality improvement, educational intervention project aimed to develop nurse leaders at a large urban federally funded Health Care for the Homeless Program (HCH), using the Nursing Leadership Institute Competency Model. Methods: A leadership seminar series which addressed six leadership topics for homeless health care nurses was developed, implemented, and evaluated using a one group pre/posttest design. The Leadership Practices Inventory (LPI) was also administered before and after the seminar series. Results: There were statistically significant increases in new skills in the areas of interpersonal skills, personal mastery, systems thinking, and finance management. LPI scores improved after completion of the leadership seminar series. Conclusion: Participation in the leadership seminar series improved leadership skills and competencies of nurse leaders at the HCH. The acquired new knowledge may prepare homeless health nurses for sustained leadership roles which in turn will result in better meeting the needs of organizations providing care to homeless individuals.